SketchInsight: Natural Data Exploration on Interactive Whiteboards Leveraging Pen and Touch Interaction - Lee, Bongshin; Smith, Greg; Henry Riche, Nathalie; Karlson, Amy; Carpendale, Sheelagh (Visualization Symposium (PacificVis), 2015 IEEE Pacific, 2015)
In this work, we advance research efforts in combining the casual sketching approach of whiteboards with the machine's computing power. We present SketchInsight, a system that applies the familiar and collaborative features of a whiteboard interface to the accurate data exploration capabilities of interactive visualizations. SketchInsight enables data analysis with more fluid interaction, allowing people to visually explore their data by drawing simple charts and directly manipulating them. In addition, we report results from a qualitative study conducted to evaluate user experience in exploring data with SketchInsight, expanding our understanding on how people use a pen- and touch-enabled digital whiteboard for data exploration. We also discuss the challenges in building a working system that supports data analytic capabilities with pen and touch interaction and freeform annotation.
Best Paper Award